Der Heeresdienst von Christen in der römischen Kaiserzeit : Studien zu Tertullian, Clemens und Origenes - Gerstacker, Andreas (2021)
This study examines the attitude of three important pre-Constantinian Church authors on the issue of military service by Christians. During their era, there were growing numbers of Christians in the army, and discussions began in their communities as to whether this was consistent with Christian beliefs. Many positions and arguments emerged. At the same time, the study shows how Christianity struggled to find its position within the Roman Empire.